Carbohydrate intake in form of gel is associated with increased gastrointestinal distress but not with performance differences when compared to liquid carbohydrate ingestion during simulated long-distance triathlon - Sareban, M.; Zügel, D.; Koehler, K.; Hartveg, P.; Zügel, M.; Schumann, U.; Steinacker, J. M.; Treff, G. (International Journal of Sport Nutrition and Exercise Metabolism, 2016)
The ingestion of exogenous carbohydrates (CHO) during prolonged endurance exercise, such as long-distance triathlon, is considered beneficial with regard to performance. However, little is known about whether this performance benefit differs among different forms of CHO administration. To this end, the purpose of our study was to determine the impact of CHO ingestion from a semisolid source (GEL) on measures of performance and gastrointestinal (GI) comfort compared with CHO ingestion from a liquid source (LIQ). Nine welltrained triathletes participated in this randomized crossover study. Each participant completed a 60-min swim, 180 min bike exercise, and a 60-min all-out run in a laboratory environment under 2 conditions, once while receiving 67.2 ± 7.2 g · h-1 (M ± SD) of CHO from GEL and once while receiving 67.8 ± 4.2 g · h-1 of CHO from LIQ. The amount of fluid provided was matched among conditions. Respiratory exchange ratio (RER), blood glucose, and lactate as well as GI discomfort were assessed at regular intervals during the experiment. The distance covered during the final all-out run was not significantly different among participants ingesting GEL (11.81 ± 1.38 km) and LIQ (11.91 ± 1.53 km; p = .89). RER, blood glucose, and lactate did not differ significantly at any time during the experiment. Seven participants reported GI discomfort with GEL, and no athlete reported GI discomfort with LIQ (p = .016). This study suggests that administration of GEL does not alter long-distance triathlon performance when compared with LIQ, but GEL seems to be associated with reduced GI tolerance. Athletes should consider this a potential disadvantage of GEL administration during long-distance triathlon.